PENGUATAN KAPASITAS KADER KESEHATAN UNTUK MENINGKATKAN DUKUNGAN SOSIAL MASYARAKAT TERHADAP KLIEN DENGAN DIABETES MILITUS - Martono; Akhmad Rifai (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2024)
Background: The estimated number of cases of diabetes mellitus in Indonesia reaches 1,017,290 cases. Central Java is one of the provinces with the third highest estimated number of cases of diabetes mellitus in Indonesia after Central Java and East Java, which is 132,565 cases. Community empowerment efforts are one of the efforts to provide social support for diabetes mellitus clients. One of the efforts to improve the quality of life of Diabetes Mellitus clients is the formation of social support for Diabetes Mellitus clients. Purpose: The purpose of this activity is to evaluate the strengthening of the capacity of health cadres in understanding Diabetes Mellitus in increasing social support for Diabetes Mellitus clients. Method: The implementation of this Community Service Program is community education in the form of health cadre training with the number of health cadre participants attending 35 people, 8 students, 4 village officials and 1 health center officer. Activities start from the planning, implementation, evaluation, to the preparation of reports. Results: Community service activities received positive appreciation from all health cadres and the Gagaksipat village government apparatus, Boyolali Regency, as well as from the health center. Based on the results of the Wilcoxon Analysis Test, there was a significant change in knowledge after being given training on diabetes mellitus (p = 0.023) and the attitude of health cadres after being given training on diabetes mellitus (p = 0.043). The plan for further activities is the socialization of diabetes mellitus by health cadres in every posyandu activity. Conclusion: Health cadre training on diabetes mellitus is able to improve the knowledge and attitudes of health cadres on diabetes mellitus, increasing social support for diabetes mellitus clients. It is necessary to optimize the role of health cadres in health activities in the community through a socialization program on diabetes mellitus so that all health services in the community are well socialized.